Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Pendidikan Agama Islam di SMPN 1 Kadipaten - Tatang Muh Nasir; Irawan Irawan; Rika Siti Karimah; Wilam Nafilah Robaeah (MANAZHIM, 2023)
By applying the Problem Based Learning Learning Model in class IX B of SMPN 1 Kadipaten Tasikmalaya Regency for Islamic Religious Education subjects, this research seeks to improve student achievement results. Descriptive research techniques are used in this type of research. All students of class IX B were used as research subjects. The learning process is carried out in three cycles, each of which has four stages, namely planning, implementing, observing, and reflecting. The Problem Based Learning (PBL) paradigm and student achievement are factors in this research. In this study, observation, questionnaires, and tests were used to collect data. Observation sheets, questionnaires, and tests as research instruments. Based on research findings from cycle I, cycle II, and cycle III, the problem-based learning activity plan planned by the teacher for class IX B of SMPN 1 Kadipaten Tasikmalaya went well. Based on the research findings, it can be said that for the 2022–2023 school year, the Problem Based Learning approach can improve student achievement in Islamic Religious Education subject class IX B of SMPN 1 Kadipaten Tasikmalaya